Zipf’s law: Divergence from general content in online communities of peers affected by attention deficit/hyperactivity disorder (ADHD) and anorexia nervosa - Livio Tarchi; Giovanni Castellini; Valdo Ricca (Advances in Medicine, Psychology, and Public Health)
Introduction: Psycholinguistics studies the relationship between linguistic behavior and psychological factors. For what concerns ADHD (Attention-Deficit/Hyperactivity Disorder) and anorexia nervosa, psycholinguistics can offer insights into the language-related aspects of these conditions. The current study aimed to describe the relationship between rank frequency and frequency of use in written corpora retrieved from internet content. Methods: Linguistic content was retrieved from online communities (Reddit). A total of 2,500 unique contributions were collected for each community (ADHD, anorexia nervosa, general content), composed of an initial script and each subsequent elicited comment. Zipf’s law was adopted to estimate the constant and exponential terms describing the relationship between word frequency rank and total usage. Results: A total of 17,853 and 10,049 written prompts were retrieved for ADHD and anorexia nervosa, respectively. This content was compared to 13,386 comments from a general community. The ADHD community exhibited a higher number of average comments per submission, while both ADHD and anorexia nervosa showed higher words per post than the general community. Zipf’s law exponential and constant terms were also higher between ADHD and anorexia nervosa compared to general content, suggesting a higher frequency of rare terms in these communities. Notably, while general content emphasized etiquette and community moderation, ADHD and anorexia nervosa discussions predominantly revolved around psychopathological terms. Discussion: This study underscores the unique linguistic characteristics within these communities, shedding light on the interplay between linguistic behavior and psychological factors in the context of ADHD and anorexia nervosa. Psycholinguistic tools could aid in the development of a better understanding of the lived experience of individuals suffering from a psychiatric disorder.